Pengaruh Belanja Modal Pemerintah dan Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi Kabupaten/Kota di Kalimantan Barat Tahun 2008 - 2012 - B01110041, SABAR JANIA (Jurnal Pembangunan dan Pemerataan, 2016)
This study , entitled influence capital expenditure and human development index on economicgrowth in 2008 - 2012 which aims to determine how much influence the government expenditure variablecapital and human development index on economic growth Regency / City in the province of WestKalimantan in 2008-2012.This research method uses multiple regression panel data is used to see the relationship betweenthe variables of government capital expenditure and human development index and economic growthRegency / City in the province of West Kalimantan in 2008 - 2012. The data used are secondary data years2008 to 2012 consisting of 13 Kabuapaten in West Kalimantan Province from the Central Statistics Agency (BPS ) and ( DJPK ).The results showed that the positive effect of government capital expenditure on economic growthbut not significant views from t values of ( 0.8309 > 0.05 ) . Human development index positive andsignificant impact on economic growth seen from the t value of ( 0.0001 < 0.05 ) . The test resultssimultaneously obtained Fstatistik value of 5.968698 with a probability value ( Fstatistik ) 0,000001lebih ofless than 0.05 ( probability < 0.05 ) . This means that economic growth is influenced by government capitalexpenditure and human development index together - together .Keywords : Government Capital Expenditure , Human Development Index , and Economic Growth.